Venom gland of Pachycondyla striata worker ants (Hymenoptera : Ponerinae). Ultrastructural characterization - Ortiz, G.; Mathias, Maria Izabel Camargo [UNESP] (Elsevier B.V., 2006)
Morphological data concerning the venom gland of worker ants of Pachycondyla striata revealed that this gland consists of three distinct regions: an external secretory portion, composed by a secretory filament that bifurcates in order to give rise to other two filaments; an internal secretory portion, represented by the convoluted gland; and a storage portion, represented by a sac-shaped reservoir. The ultrastructural analysis showed that the reservoir is enveloped by a simple pavementous epithelium, coated internally with a cuticle. The external secretory portion is composed by cells forming a simple cubic epithelium, in which the apical portion presents numerous microvilli while the basal portion of the cells shows infoldings of the plasma membrane containing numerous mitochondria. The convoluted gland possesses cells of irregular morphology with nuclei containing condensed chromatin, suggesting inactivity. However, these cells are in fact undergoing secretory activity, which is probably added to the final secretion produced by the gland. The cytoplasm of these cells contains several elements distributed therein, such as ribosomes and polyribosomes, lipid droplets, and protein inclusions in the form of crystals, thus Suggestive of protein storage, which would be used by the insect when metabolically required. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: ants; venom gland; convoluted gland; protein crystals; Ponerinae; Pachycondyla striata